2005
DOI: 10.1002/app.22397
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a biodegradable polyester elastomer with thermal processing abilities

Abstract: ABSTRACT:We studied the condensing reaction of sebacic acid and glycerol and prepared biodegradable elastomers. Swelling experiments proved that the elastomers were crosslinked polyesters consisting of both insoluble parts (gel) and soluble parts (sol), but the content of sol was higher than gel. X-ray diffraction analysis showed that some ordered and crystallized structures existed in most of the elastomers. Differential scanning calorimetry measurement showed that there were both crystal regions and amorphou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…Inspired by the success of Wang's group, and in an effort to explore the thermoplastic property of the elastomer, which would be very beneficial to processing of the material, we have also conducted studies of the preparation of the PGS elastomers based on glycerol and sebacic acid. 28 We have found that the product has a certain thermal-moldable ability that can be achieved at a different molar ratio, but the overall properties of the elastomer still need improvement. In the present work, a two-step preparation method is put forward as shown in Figure 1; the thermoplastic elastomer (TMPGS) is obtained in a similar manner.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Inspired by the success of Wang's group, and in an effort to explore the thermoplastic property of the elastomer, which would be very beneficial to processing of the material, we have also conducted studies of the preparation of the PGS elastomers based on glycerol and sebacic acid. 28 We have found that the product has a certain thermal-moldable ability that can be achieved at a different molar ratio, but the overall properties of the elastomer still need improvement. In the present work, a two-step preparation method is put forward as shown in Figure 1; the thermoplastic elastomer (TMPGS) is obtained in a similar manner.…”
Section: Introductionmentioning
confidence: 96%
“…As a result, the gel content of TMPGS increases, strength and elongation become greater, and the in vitro degradation rate is slower, as compared with the results obtained at the same molar ratio of reactants in our previous study. 28 Research on TMPGS elastomers prepared by the two-step method may greatly extend the development of PGS elastomers in the biomaterial fields.…”
Section: Introductionmentioning
confidence: 99%
“…According to Yang et al the POC elastomers show inflammatory response that is similar to that shown by a standard PLGA with minimal fibrous capsule formation [3]. Apart from their easy thermal processabilities [12], the properties of elastomeric citrates could also be tailored by mixing them with natural bone mineral hydroxy apatite (HA) [10] or with PLLA [13] in order to meet specific tissue regeneration requirements.…”
Section: Introductionmentioning
confidence: 98%
“…To achieve PGS elastomers with thermoplasticity, we first prepared PGS elastomers composed of a sol and a gel by a one-step method without the assistance of a solvent 15 and then put forward a two-step method. 16 Using the two methods, we can obtain thermoplastic poly(glycerol sebacate) (TMPGS) elastomers, and we have found that the two-step method is easy to control and can optimize the properties of materials.…”
Section: Introductionmentioning
confidence: 99%